2000
DOI: 10.2307/1170786
|View full text |Cite
|
Sign up to set email alerts
|

Students' Need for Belonging in the School Community

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. American Educational Research Association is collaborating with JSTOR to digitize, preserve and extend access to Review of Educational Research.Defining sense of community as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

43
764
0
82

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 536 publications
(889 citation statements)
references
References 37 publications
43
764
0
82
Order By: Relevance
“…Group cohesiveness is the tendency of a CSCL group to have a sense of unity while working on the group tasks and to satisfy the emotional needs of its members (Carron & Brawley, 2000). A feeling of belonging-the feeling that one is connected and accepted by the other CSCL members-is important as it gives the group members a group identity (Goodenow, 1993;Osterman, 2000). Trust is defined as the cognitive and affective assurance of group members that they respect each other's interests and, therefore, can orient themselves toward each other's words, actions, and decisions with an easy conscience (Chang & Lee, 2007;Emans, Koopman, Rutte, & Steensma, 1996).…”
Section: Social Spacementioning
confidence: 99%
“…Group cohesiveness is the tendency of a CSCL group to have a sense of unity while working on the group tasks and to satisfy the emotional needs of its members (Carron & Brawley, 2000). A feeling of belonging-the feeling that one is connected and accepted by the other CSCL members-is important as it gives the group members a group identity (Goodenow, 1993;Osterman, 2000). Trust is defined as the cognitive and affective assurance of group members that they respect each other's interests and, therefore, can orient themselves toward each other's words, actions, and decisions with an easy conscience (Chang & Lee, 2007;Emans, Koopman, Rutte, & Steensma, 1996).…”
Section: Social Spacementioning
confidence: 99%
“…Les élèves qui ressentent du soutien et de l'attention de la part de leur enseignant se disent plus motivés (Goodenow, 1993 ;Maulana, Opdenakker et Boske, 2014 ;Murdock et Miller, 2003) et ont un meilleur rendement scolaire (Goodenow, 1993 ;Midgley, Feldlaufer et Eccles, 1989). Inversement, les élèves qui rapportent des conflits avec leur enseignant se disent moins motivés et réussissent moins bien à l'école (Hamre et Pianta, 2001 (Finn et Rock, 1997 ;Osterman, 2000 ;Wang et Pomerantz, 2009). Enfin, selon Hamre et Pianta (2005), la qualité des interactions quotidiennes dans la classe, sous forme de soutien émotionnel de l'enseignant, atténuerait le risque d'échec scolaire précoce.…”
Section: Contexte Théoriqueunclassified
“…Middle schools are multifaceted social settings that present diverse opportunities for students to experience social connectedness. Students develop a sense of belonging, which reflects their general feelings of being valued, accepted, safe, and connected to others within the school community (Goodenow & Grady, 1993;Osterman, 2000). While sense of school belonging is the affective tie that students maintain to their schools on the whole, students also have relational experiences that connect them socially to the school, including acceptance from peers and integration into the peer group system of the sixth grade.…”
Section: The Role Of Relatedness In Students' Perceived Transition Exmentioning
confidence: 99%
“…Many studies have demonstrated the connection between students' sense of school belonging, or feeling socially supported and accepted in school, and positive middle school adjustment (Goodenow & Grady, 1993;Juvonen, 2006;Osterman, 2000). Transitioning middle school students begin school with familiar and unfamiliar peers as well as new rules, expectations, and teachers (Hardy et al, 2002).…”
Section: Social Integration and Students' Transition Experiencesmentioning
confidence: 99%